STUDY ON THE EFFECT OF TRANSITION METAL DOPING ON OXYGEN EVOLUTION REACTION ACTIVITY ON NICKEL PHOSPHATE SURFACES USING DENSITY FUNCTIONAL THEORY COMPUTATION - Priyo Darminto, Riyadi
Supporting PLN’s goal of achieving Net Zero Carbon Emissions by 2060, the development of hydrogen production technology as green energy must be enhanced to become more economical and efficient. Currently, platinum and iridium are standard materials for the anode and cathode in water electrolysis cells, exhibiting optimal performance but high costs. Consequently, research on alternative, more affordable, and stable materials, such as alloys based on nickel, manganese, and cobalt, has been actively pursued. Several studies, both simulations and experiments, have shown that these metal alloys exhibit low overpotential values and high current density, indicating promise as anode materials for electrolysis cells. In this study, nickel phosphate (Ni?(PO?)?) Facet 100, referred to as NiPO(100), was tested as an anode material in the simulation of the Oxygen Evolution Reaction (OER). To reduce potential energy, transition metal dopants were introduced by substituting one Ni atom on the NiPO(100) surface, creating NiPO(100)-M, where M represents Mn, Fe, Cu, and Co. Simulations were conducted by placing O, OH, OOH, H?O, and O? molecules as OER intermediates on both the Ni and dopant atoms on the pristine NiPO(100) surface and NiPO(100)-M. All simulations in this study were carried out using Quantum Espresso software under the Density Functional Theory (DFT) framework. The results demonstrate that transition metal doping generally enhances OER performance compared to the pristine NiPO(100) surface, with most dopants lowering the overpotential values. The observed trend in overpotential values aligns with the O adsorption energy on the doped surfaces. Despite the addition of transition metals, the electronic profile of surface Ni atoms remains largely unchanged, leading to similar overpotential values at these sites. OER activity is primarily influenced by the localized electronic states of the embedded transition metal dopants. The performance ranking based on average overpotential values shows that Mn and Fe dopants exhibit the highest activity, followed by pristine nickel phosphate, Co doping and finally Cu doping. Keywords: water electrolysis, oxygen evolution reaction, nickel phosphate, transition metal doped, DFT